The effects of memory and social strategies on oral production - Henríquez, Tania Katina; Von Johnn, Harry Ignacio; Peña, Víctor Hugo; Llanquileo, Elena Adriana (Colombian Applied Linguistics Journal, 2017)
Language learning strategies (LLS) play a significant role in enhancing learning (Hedge, 2000; Oxford, 1990, 2003). In spite of this, little attention has been given to LLS in oral production in English as a second language (ESL) in Chile. This quasi-experimental research aimed to improve learners’ oral production achievements through a direct instruction period (DIP) of memory and social learning strategies. The participants included 10 eleventh grade students from a state-subsidized school. Both qualitative and quantitative instruments were used to collect data including: ethnographic field notes, surveys, and a pre/post-test. Moreover, due to sample size, non-parametric statistics were used to analyze the results obtained from the pre- and post-tests. Results showed that students’ oral production improved as a result of the memory instruction and social strategies suggesting that the former is more influential than the latter. These findings also suggest that a change in teaching methodologies and sample size might have influenced the results.